Introduction to Looked Class, Talked Red by Barbara Harlow. (January 2019) - Hoad, Neville
The author remembers his friend and colleague Barbara Harlow and provides an introductory context for the selection from her book-in-progress on Ruth First published in this special issue of Race & Class 60, no. 3 (2019). He describes just how Ruth First became of interest to Harlow, explaining the intersections of Ruth First's personal history as a public intellectual with the history of decolonisation and the anti-apartheid movement, and the intersection of a 'public' and 'private' or domestic life. He speculates as to why the project of over thirty years remained unfinished in terms of a final publication.